Clinical evaluation and power Doppler sonography in rheumatoid arthritis: Evidence for ongoing synovial inflammation in clinical remission - Ozgocmen, Salih; Ozdemir, Huseyin; Kiris, Adem; Bozgeyik, Zulkif; Ardicoglu, Ozge (Lippincott Williams & Wilkins, 2008)
Objective: This study proposed to assess the relationship between power Doppler ultrasound examination and spectral Doppler analysis of hand joints with clinical and laboratory parameters in rheumatoid arthritis. Methods: Patients receiving disease-modifying antirheumatic drugs or biologics (infliximab) underwent joint examination and were assessed by a Health Assessment Questionnaire, Duruoz's Hand Index, and Hand Function Test. All were categorized for disease activity using the American College of Rheumatology and disease activity score 28-joint (DAS28) criteria. Ten metacarpophalangeal joints and 4 wrist joints (ulnar-carpal and radiocarpal joints) in each patient were examined by power Doppler and spectral Doppler. Flow signal in the synovium was semiquantitatively graded. A cumulative flow signal score (CFS) and mean resistive index (RI) was calculated in each patient. Results: Patients with active disease had significantly higher CFS compared with patients with inactive disease, but the mean PI was similar. Health Assessment Questionnaire, Duruoz's Hand Index, Larsen, and DAS28 scores correlated significantly with CFS, but the erythrocyte sedimentation rate and C-reactive protein scores did not. Mean RI did not correlate with clinical or laboratory parameters. A majority of patients who were in clinical remission according to American College of Rheumatology or DAS28 criteria had ongoing synovial inflammation on power Doppler ultrasound (58% and 62%, respectively). Conclusion: Power Doppler examination of rheumatoid hand joints is a practical method to estimate synovial inflammation. A modification of current remission criteria by combining imaging techniques with clinical and laboratory examination may be conceivable. These results underscore the necessity of more sophisticated research, assessing the agreement between long-term Doppler changes and clinical parameters.
Keywords: disease activity; power doppler; rheumatoid arthritis; spectral Doppler